INFIDELS IN ENGLISH LEGAL THOUGHT: CONQUEST, COMMERCE AND SLAVERY IN THE COMMON LAW FROM COKE TO MANSFIELD, 1603–1793. (August 2019) - CAVANAGH, EDWARD
Abstract : English common law reports are dense with ideas. Yet they remain mostly untapped by intellectual historians. This article reveals how intellectual history can engage with law and jurisprudence by following the notion that "infidels" (specifically non-Christian individuals) deserved to receive exceptional treatment within England and across the globe. The starting point is Sir Edward Coke: he suggested that infidels could be conquered and constitutionally nullified, that they could be traded with only at the discretion of the monarch, and he confirmed their incapacity to enjoy full access to the common law. This article uncovers how each of these assertions influenced the development of the imperial constitution in the seventeenth and eighteenth centuries, when it came to war, trade and slavery. Identifying each of the major moves away from Coke's prejudices, this article argues that sometimes common lawyers responded to political change, but at other times anticipated it.